Kepemimpinan Agile Kepala Sekolah dalam Meningkatkan Mutu Sekolah di Daerah Terpencil: Analisis Systematic Literature Review - Khalifah, Hamidatul; Santosa, Heru; Listyasari, Winda Dewi; Takdir, Muh.; Syam, Aldo Redho (Proceeding of Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2025)
This study analyzes the implementation of agile leadership in improving school quality in remote areas during the 2015–2025 period through a PRISMA 2020–based Systematic Literature Review. Literature was collected from Scopus, ERIC, and Google Scholar, with 25 articles meeting the inclusion criteria. The data were analyzed descriptively and thematically to identify research trends, agile leadership practices, implementation challenges, and their impact on school quality. The quality of the studies was assessed using the Mixed Methods Appraisal Tool to ensure methodological consistency. The findings show a significant increase in research after 2020, with a shift from conceptual discussions toward practical implementation. Agile leadership is implemented through iterative decision-making, collaboration, flexible learning management, teacher empowerment, and innovative use of local resources. This approach strengthens school culture, enhances teacher performance, and provides solutions to geographical barriers. Supporting factors include community collaboration and teacher commitment, while key challenges involve limited technology and insufficient professional training.